Le silence et l’oubli - Maria Hansson (Les Cahiers de Framespa)
One of the peculiarities of Swedish literature of the late 19th century is the presence of many female authors. In contrast to French naturalism, which is not represented by any woman, the contemporary movement of Modern Breakthrough is marked by the dazzling but ephemeral success of women’s works. Through a study of the reception of women’s literature, this article aims to question the eclipse of Swedish female naturalist authors doomed from 1890 to silence and oblivion.